Hydrogen sulfide (H₂S) leak risk management in gas plant facilities: A review article - Didik Mustakim; Gilang Arya Ramadhan; Zakir Husin; Achmad Jusuf Zulfikar (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
Hydrogen sulfide (H₂S) is a highly toxic and corrosive gas frequently encountered in oil and gas processing operations, particularly in gas plant facilities. Due to its hazardous nature, even minimal leakage can result in fatal consequences for personnel, severe environmental contamination, and major disruptions to plant operations. This review article aims to systematically examine the current risk management practices applied to control H₂S leakage in gas processing facilities. A comprehensive literature review was conducted on 30 peer-reviewed scientific articles published between 2015 and 2024, sourced from reputable databases such as Scopus, ScienceDirect, and Google Scholar. The analysis reveals those structured methodologies, such as the ISO 31000 risk management framework, HAZOP (Hazard and Operability Study), HAZID (Hazard Identification), and bowtie analysis, are effective in identifying vulnerable points within H₂S processing and distribution systems. Furthermore, the adoption of automated H₂S gas detection systems, regular emergency response drills, safety training programs, and the use of corrosion-resistant materials significantly enhances risk mitigation. The findings emphasize the need for integrated approaches that combine technical safeguards with organizational safety culture. This article provides essential insights for industry practitioners and policymakers to improve safety standards and reduce the likelihood and impact of H₂S-related incidents in gas plants.